Studi Pendahuluan: Inventarisasi Amfibi di Kawasan Hutan Lindung Bukit Cogong II - Doni Setiawan; Indra Yustian; Catur Yuono Prasetyo (Faculty of Mathtmatics and Natural Sciences, 2016)
Which one big islands in Indonesian was have high biodiversity value is Sumatera Island. There was Amphibian groups. Amphibians class is one of the constituent components of the ecosystem which has a very important role, both ecologically and economically. Based on preliminary studies in the area of Protected Forest Cogong II Hill has been done survey in October 2015 showed the extent of damage, it's evident from the many of rubber plantation land clearing by the society which can impact negatively on the environment, especially the habitat of amphibian. So, inventory of amphibians in the Cogong Hill II protected forest areas need to be done. Observation of amphibian directly through using Visual Encounter Survey (VES) method. The results of the survey was found 10 species in to 5 families and 1 ordo. There is Bufonidae family : Bufo asper, Bufo melanosticus, Bufo biforcatus, Ranidae family is Hylarana baramica and Rana chancolnota, Dicroglossidae family is Fejevarya limnocharis, Fejevarya cancrivora, Limnonectes sp., Rhacophoriidae family is Polypedates leucomystax and Microhylidae family is Kaloula baleata. Based on IUCN status category from 10 amphibians species was found in the region, all species have Least Concern Status.